Expo Research Psychology, A Multidisciplinary Experience (UNIHumanitas, 2013)
Multidisciplinarity is a vital issue for university education. This article presents a methodology of multidisciplinary work carried out among four subjects of the first year of Psychology. Efforts were unified to promote bibliographic and experimental research in a group of 40 students, increasing their interest in research and their motivation to study the career.
Keywords: multidisciplinary; experimentation; psychology; research